Predictive factors of unsatisfactory evolution among 20-65 year-old patients infected with COVID-19 - Alexander Sosa Frias; Aimara de la Caridad Vergara Santos; Oreste Mojena Mojena (Universidad de Ciencias Médicas de La Habana, 2021)
Introduction: Several authors validated the use of clinical, humoral, and radiological indicators as predictors of unsatisfactory evolution in patients with COVID-19. Objective: To evaluate the clinical-humoral variables and the findings in the first chest x-ray as predictors of unsatisfactory evolution in patients with COVID-19. Material and Methods: An observational and retrospective case-control study was carried out in 484 patients infected with COVID-19 admitted to the Cuban Hospital of Qatar between March and July 2020. The sample was composed of 60 patients. Cases: patients with respiratory failure who required invasive ventilation or death. Controls: patients with COVID-19 without complications. Input variables: age, sex, BMI, presence of comorbidities, leukocyte value, and severity index of the first chest x-ray. Response variable: clinical evolution. The bivariate analysis was performed using the Chi-square test. In the multivariate analysis, using binary logistic regression, p values lower than 0.05 were considered significant. The results were expressed in the Odds Ratio. Results: The progression of age, belonging to the group of 61-65 years, female sex, suffering from diabetes or arterial hypertension, having two comorbidities, abnormal leukogram, and the severity index of the first chest X-ray between 2-6 / 6 were related to unsatisfactory evolution. The leukogram (ODDS RATIO 68.634 p = 0.000) and the severity index of the first chest x-ray (ODDS RATIO 12.201 p = 0.008) have an independent influence on patients with COVID-19. Conclusion: The predictive value of the leukogram and the severity index in the first chest x-ray over unsatisfactory evolution were demonstrated in these patients.